Fuzzy Pole Placement for Speed Control in D.C. Motor - Kharabian, B.; Shahri, A.R. M.; Mashhadi, S.K. Mousavi; SamSaam, S. (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: In this paper, fuzzy pole placement control approach is proposed to control the speed of D.C motor. In this method, state feedback gain is tuned by fuzzy logic. Methods: In conventional pole placement control, constant gain is considered to insert the poles of system in the desired place. Therefore, unnecessary effort is appliedto the system, and the system implementation becomes costly. In contrast, in fuzzy pole placement control, poles of system alter gradually based on the performance of system and are settled in desired point causing the system to display apposite performance. In other words, in conventional pole placement, a determined pair of poles exists, whereas in fuzzy pole placement method, an area, in which a pair of poles is relocated is obtained. Pair of poles changes its place based on the recent behavior of the system to have more appropriate manner. Results: As a result, state feedback gain changes intelligently according to the on-line performance of system eventuating in acceptable outcomes. Results show that this approach is effectual and sound.
Keywords: D.C motor